The several faces of the medicalization of birth. Italy and its peculiarities - Spina, Elena (Frontiers in Sociology, 2023)
Background: Medical-scientific advances in maternal care gradually improved the health of mothers and new-borns. However, this has contributed to increasing levels of medicalisation, defined as the overuse of medical interventions even in low-risk pregnancies and childbirths. In Italy pregnancy and birth still appear to be rather medicalized than in the rest of Europe. Moreover, the uneven distribution of these practice over the territory appears to be evident. The purpose of this article is to both highlight and explain the Italian peculiarity in terms of high medicalization of childbirth and its territorial variability. Theoretical framework: the extensive literature on medicalization of childbirth was systematized by Christiaens and Van Teijlingen (2009) who use childbirth as a case study to distinguish four meanings of medicalisation, by classifying them into two generations of theories. Alongside this literature several studies attempted to interpret differences in maternity model of care showing the important role played by path dependence. Results: In the European scenario, Italy stands out for its high percentage of caesarean sections, but also for its excessive recourse to antenatal visits during pregnancy and the application of interventions during labour and vaginal births. Going into regional detail, however, Italian situation appears rather uneven: relevant differences emerge in relation to medicalization of both pregnancy and birth. Discussion: the article explores the possibility that areas whit different sociocultural, economic, political and institutional background may have introjected different meanings of medicalisation, thus reproducing different maternity models of care. In fact, the simultaneous presence, in Italy, of four different meanings of medicalisation seems to be rooted. Even with some similar traits, different conditions and situations emerge in different geographical areas, leading to the prevalence of one meaning rather than another and resulting on different outcomes in terms of medicalisation. Conclusion: The data presented in this article seem to deny the existence of a national maternity model of care and. On the contrary, they confirm the idea that medicalization is not necessarily linked to the different health conditions of mothers in different geographical areas and that a path dependent variable is able to explain it.